Efektivitas Penerapan Model Pembelajaran Group Investigation Dalam Upaya Meningkatkan Aktivitas Belajar Siswa - Herlina; Erliany Syaodih; Bella Anantha Sritumini (EDUCARE, 2012)
This is one of the causes of student learning activities that are low, activity is a form of behavior which is a manifestation of interest. Manifestations of such behavior is the tendency of a person to believe or otherwise of an object, activity or job. Things that cause inactivity of students in the learning process is learning problems both internally and externally and can be studied from the dimensions of the teacher and student dimension. Other causes that can be disclosed are reviewed from the stages, learning problems can occur at the time of learning, during the learning process and after learning. Overcoming the demands of current learning, teachers need to make a learning design that is suitable to be applied in order to improve learning activities. Cooperative Learning models that are suitable to be applied to accounting subjects are using the Group Investigation model, students are given responsibility for their work, individually, in pairs or in groups. So by using this learning model students are required to be able to encourage and guide students in the learning process is very essential.